Practical wellbore hydraulics and hole cleaning : unlock faster, more efficient, and trouble-free drilling operations - Ramsey, Mark S. (Gulf drilling guides., 2019)
Practical Wellbore Hydraulics and Hole Cleaning presents a single resource with explanations, equations and descriptions that are important for wellbore hydraulics, including hole cleaning. Involving many moving factors and complex issues, this book provides a systematic and practical summary of solutions, thus helping engineers understand calculations, case studies and guidelines not found anywhere else. Topics such as the impact of temperature and pressure of fluid properties are covered, as are vertical and deviated-from-vertical hole cleaning differences. The importance of bit hydraulics optimization, drilling fluid challenges, pressure drop calculations, downhole properties, and pumps round out the information presented. Packed with example calculations and handy appendices, this book gives drilling engineers the tools they need for effective bit hydraulics and hole cleaning operation design.